Prospects for the development of cognitive technologies based on the principles of the SMART-CITY concept - Tkachenko, V.; Tugay, А.; Klymchuk, M. (Ways to Improve Construction Efficiency, 2020)
The article focuses on the problems of smart and sustainable urban planning in the context of urbanization, which is the basis for the development and implementation of the "smart-city" concept. The relevance of the study of the Smart City concept in the context of the spread of the use of cognitive technologies in different spheres of society is conditioned by the growth of information volumes, the intensive development of digital technologies, their introduction into the work of different institutions. Analyzing the Concept of Digital Economy and Society of Ukraine for 2018-2020, it is highlighted that the introduction of digital innovations in the creation of IT infrastructure for processing big data, training professionals to work with "smart" systems on the basis of cognitive technologies will ensure sustainable growth, accelerate social -economic, technological development; improve living standards; will create conditions and opportunities for self-realization of each person. The driver of innovative economic development and socio-economic progress is the introduction of information and communication technologies, on the basis of which effective management principles, approaches, methods, tools, technologies and strategy of state development are formed. Based on the results of the theoretical analysis of the basic definitions of "smart-city", the author's vision of this concept is proposed. The main tasks of the Smart City implementation with consideration of the development of cognitive technologies are highlighted. Specific social development programs based on NBIC technologies have been adopted in America and Europe. The synergy of components of NBIC technology is nowadays considered the basis of social progress, and cognitive technology is an important component of it. In today's urbanization, attention is paid to the problems of smart and sustainable urban planning, which is the basis for the development and implementation of the concept of "smart-city". The research made it possible to isolate the following problems in the implementation of smart-city, among which organizational, managerial, financial, economic and infrastructure are crucial.